Do integrated economies grow faster? evidence from domestic equity holdings - Lee, Pei Ling; Chin, Lee; Law, Siong Hook; Saini, Azman (Economics Bulletin, 2017)
This paper aims to investigate the impact of financial integration on economic growth. Home bias, which is the tendency of over-investing in domestic stock bourse, is proposed as a proxy of advanced financial integration. The persistence of home bias reflects the existence of international friction. A high degree of home bias reflects imperfect integration of the national stock market with world capital markets and suggests a slower pace of economic expansion. Home bias is utilised, through its own lags, to address the reverse causality implied by potential endogeneity between home bias and real GDP growth. A dynamic GMM approach is employed to address the endogeneity and serial correlation concern. The results indicate the lagged real GDP per capita growth, home bias, government consumption, and variability in real effective exchange rates are found to explain cross-country variation in growth.